Implementasi Program Kesejahteraan Sosial Anak ( PKSA ) untuk Kemandirian Anak Jalanan di Rumah Singgah Anak Mandiri, Umbulharjo, Yogyakarta - , SAIFUL RAHMAN PASARIBU; , Milda Longgeita Br Pinem, S.Sos, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Social Changes in children has increased dramatically in the streets that tend to cause a lot of problems affecting public unrest . It also brings an increase in the basic needs of street children and a variety of support programs to save children from the streets . The problem is that many street children are still not getting the social welfare programs of direct aid children ( PKSA ) who have no children at home stopped autonomy . With the availability of child welfare programs at home stopped , children rescued from the streets and can be guided properly when the child is in shelter homes autonomy . The research looked at how social welfare programs affecting children street children independence after joining a regular target children and empowerment training provided by the caretaker and companion sosial.Metode used in this study is kualitatif.Data method used is primary data and data sekunder.Penelitian field to obtain primary data through interviews and secondary observasi.Data obtained through library and documentation . Informants in this study there are 7 people with the details of four children who live permanently in a halfway house , and three children do not live in a halfway house autonomy child , Umbulharjo , Yogyakarta. From the research conducted , it is known that the service provided in the form of services from shelters physical and non-physical , ie food , clothing , shelter , health , mental and psychological monitoring street children . Existing services in a halfway house has not been matched by the availability of complementary infrastructure to support the success of training programs and child welfare programs . However, in the implementation of social welfare programs the child has been running well in a halfway house , transit house into a playground and learning for street children . Social and moral support provided through the shelters to help the formation of character in realizing emotional and mental child langsung.Namun independence issues to the attention of a child less variety among the local people who regard them as a child who always pose problems of their areas , the need for awareness of the whole parties so that the child does not become a problem which troubled by the public .